Perioperative Aspirin for Prevention of Venous Thromboembolism: The PeriOperative ISchemia Evaluation-2 Trial and a Pooled Analysis of the Randomized Trials. Issue 2 (April 2017) - Eikelboom, J. W.; Kearon, C.; Guyatt, G.; Sessler, D. I.; Yusuf, S.; Cook, D.; Douketis, J.; Patel, A.; Kurz, A.; Allard, R.; Jones, P. M.; Dennis, R. J.; et al.
Abstract : (Abstracted from Anesthesiolog, 125(6):1121–1129, 2016) Venous thromboembolism (VTE) occurs in 1% to 5% of noncardiac surgery patients in the 30 days following surgery without the use of routine thromboprophylaxis, thereby emphasizing the importance of postoperative VTE prevention. Aspirin is generally preferred over other anticoagulants because of its low cost and because it is already being taken by many patients preoperatively.